Cereals market: A focus on Italian import and price volatility in a war period - Roberto Solazzo; Federica De Maria; Alessandra Pesce (Italian Review of Agricultural Economics (REA), 2023)
The conflict between Ukraine and Russia raises several questions and uncertainty about the cereal supply chain and market trends. This international crisis and other factors influencing the market, such as the environmental and climate ones, have placed greater attention on Italy's dependence on foreign countries for some important products for our agri-food industry, including cereals and feed for the livestock sector. The Italian pasta industry, as well as bakery products, need a constant and large supply of wheat, which often comes from foreign markets. This also applies to the livestock sector, with relevant imports of raw materials from abroad for the feed sector. International events also affected Italian cereal imports, although Italy does not strongly depend on the Black Sea for these products. This article provides an analysis of the Italian import of cereals in the recent period when market instability linked to the conflict and other factors emerged. The study also focuses on the forecast for the future and on the role of price dynamics.
Keywords: F01; F51; Q11; 330; Black Sea Grain Initiative; cereal prices; cereal products; forecasting; Italian imports